Drought priming improves tolerance of Alhagi sparsifolia to subsequent drought: A coordinated interplay of phytohormones, osmolytes, and antioxidant potential - Ullah, Abd (2024)
Perennial trees are often stressed by drought more than once during their life cycle. Our study exposed three-month-old Alhagisparsifolia, with (drought-primed) or without (nonprimed) prior drought stress to subsequent drought for two months, aiming to reveal whether pre-exposure to drought could enhance seedling resistance to subsequent drought and investigated possible underlying mechanisms. Root biomass, leaf relative water content, chlorophyll a, and carotenoids were significantly higher in drought-primed than nonprimed seedlings. They also had reduced concentrations of malondialdehyde, hydrogen peroxide (H2O2), and superoxide anions (O2•−), indicating relief from oxidative stress. This relief was associated with a coordinated upregulation of enzymes scavenging O2•−and H2O2, particularly superoxide dismutase (SOD) and catalase (CAT), and the maintenance of the ascorbate-glutathione (AsA-GSH) redox pool and enzymatic activities (ascorbate peroxidase, mono- and dehydroascorbate reductase, and glutathione reductase), leading to the better regulation of reactive oxygen species. The failure of nonprimed seedlings to upregulate the SOD, CAT, and AsA-GSH cycles nevertheless made the seedlings susceptible to oxidative stress. The increased levels of strigolactones, jasmonic acid, and abscisic acid in drought-primed seedlings reveal their roles in subsequent stress. They also displayed higher gibberellic acid and indole acetic acid. A principal component analysis showed that the seedlings responded differently to drought if they had previously suffered a drought, mainly due to a higher capacity for pigment protection, oxidative scavenging, osmolytes, and anti-stress hormones. Our study provides insights into the benefits of stress memory induced in seedlings by early drought priming as a strategy for overcoming subsequent stress.